Desenvolvimento e caracterização de micro/nanossuspensões com propriedades mucoadesivas para liberação cólon-específica de metotrexato - Santos, Aline Martins dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The methotrexate (MTX) is pH-dependent solubility drug used in the treatment of gastrintestinal diseases, such as Crohn's disease, ulcerative colitis and colorectal carcinomas. The micro/nanosuspensions development is a promising strategy to incorporate this type of drug, since it offers important advantages, such as particle size reducing of drug, which may lead to the increase of the dissolution and permeability rates of the drug. Additionaly, responsive-polymers can undergo in situ sol-gel phase transition, promoting mucoadhesion process followed by a greater retention of system in the action site. In this sense, the aim of this work was to develop micro and nanosuspensions associated to mucoadhesive polymers for colon specific release of MTX. The particles were obtained from Bottom-up method by acid-base reactions, employing the Ultra- Turrax or Sonicator and hydroxypropylmethylcellulose (HPMC) and poloxamer 407 (P407) as stabilizing. Polyacrylic acid (PAA), poloxamer 407 and gellan gum, which have different mucoadhesion mechanisms (pH, temperature and ionic concentration) were incorporated. The physic-chemical characterization of micro/nanosuspensions was realized by light scattering, measurement of zeta potential, scanning electron microscopy (SEM), texture profile analysis (TPA) and ex vivo mucoadhesion test. In the bottom-up method, the conditions were optimized to reach the solubilization and, mainly, the precipitation of drug. This variation in precipitation conditions showed that increasing the acid proportion is possible to modulate the particle size to the micro/nano-range, in the absence of stabilizer. The nanosuspensions exhibited pH above 5.0, while the microsuspensions below 4.0. For microsuspensions, analysis of the results showed that depending on the stirring process and type of stabilizer used it was possible ...

O metotrexato (MTX) é um fármaco com solubilidade pH dependente, utilizado no tratamento de doenças do trato gastrointestinal, como a doença de Crohn, retocolite ulcerativa e carcinomas colorretal. O desenvolvimento de micro/nanossuspensões podem ser uma estratégia promissora para incorporação de fármacos que possuem solubilidade pH dependente, oferecendo vantagens como a redução do tamanho da partícula do fármaco que pode levar ao aumento da taxa de dissolução e da permeabilidade. Adicionalmente, polímeros estímulo-responsivos podem sofrer transição de fase sol-gel in situ, promovendo a mucoadesão e uma maior retenção do sistema no local de ação. Dessa forma, o objetivo deste trabalho foi desenvolver micro/nanossuspensões contendo polímeros mucoadesivos para liberação cólon-específica do MTX. As partículas foram obtidas pelo método Bottom-up, utilizando reações de ácido-base e estabilizadas com hidroxipropilmetilcelulose (HPMC) e poloxâmero 407 (P407), através de agitação em Ultra-turrax ou Sonicador. Foram incorporados polímeros derivados do ácido poliacrílico como, Carbopol® ETD 2020 e Ultrez 10NF, poloxâmero 407 e goma gelana, pois estes polímeros atuam por diferentes mecanismos na mucoadesão como pH, temperatura e concentração iônica. A caracterização fíquico-química das micro/nanossuspensões foi realizada por espalhamento de luz, medida do potencial zeta, microscopia eletrônica de varredura (MEV), análise de textura (TPA) e ensaios de mucoadesão ex vivo. No método Bottom-up foram otimizadas condições para alcançar a solubilização e principalmente a precipitação do fármaco. Essa variação nas condições de precipitação, demonstrou que o aumento da proporção de ácido, permite modular o tamanho da partícula para a escala micro/nanométrica, na ausência...
Keywords: Inflammatory bowel deseases; Doenças inflamatórias intestinais; Proctocolite; Metotrexato; Cólon (Anatomia) – Câncer; Farmacologia